Lean Supply Chain Management and its Impact on Competitiveness - Papageorgiou, George; Efstathiades, Andreas; Dimitriadis, Theodoros (International Journal of Supply Chain Management, 2020)
Due to the increased competition in the business environment and the constant changes in consumer demands and needs, companies should be characterized by adaptability, flexibility, as well as strategic and operational alignment between the different links in their supply chain. However, knowledge is inadequate about the way in which lean supply chain management should be implemented. Such knowledge is more limited even in some developed countries. The aim of this research is to examine the relationship between the implementation of lean supply chain management and business competitiveness. To achieve this, a survey was distributed to businesses of the Greek economy that currently goes under major changes. One important finding was that lean supply chain management leads to a strong competitive advantage, especially through cost and waste reduction. Further, it was found that lean supply chain management results in meeting customer requirements, increased profitability, reduction of inventory levels, the introduction of just-in-time systems and increased sustainability. However, organizational structure, employees’ resistance to change, organization’s rules, procedures and policies, as well as lack of robust and professional relationships with suppliers, are obstacles to be overcome when implementing lean supply chain management systems.